Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1177/014556139807700309
|View full text |Cite
|
Sign up to set email alerts
|

Revision Endoscopic Sinus Surgery: The Thomas Jefferson University Experience

Abstract: Since its introduction, functional endoscopic sinus surgery (FESS) has demonstrated success rates of 76% to 98%. A small group of the patients in whom initial FESS and optimal medical therapy fail require revision endoscopic sinus surgery (RESS). This group has recently been studied by several authors, and we have evaluated a group of 90 RESS patients selected from 753 consecutive primary FESS patients. Patients were followed for a mean of 22.8 months. Extent of disease, history of polyps, allergy, previous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 25 publications
1
50
0
1
Order By: Relevance
“…Functional endoscopic sinus surgery has become the standard procedure to restore sinus ventilation and drainage by opening the key areas while preserving sinus mucosa. An overall success rate of 85% is reported in primary functional endoscopic sinus surgery, with a 2% to 24% failure rate because of recurrence of disease or poor healing because of persistent infl ammation and/or bacterial colonization [46,47]. In approximately 18% of patients, poor healing is linked to abnormal scarring, superinfection, and fi brosis formation, with these complications potentially leading to revision surgery [48].…”
Section: Treatmentmentioning
confidence: 99%
“…Functional endoscopic sinus surgery has become the standard procedure to restore sinus ventilation and drainage by opening the key areas while preserving sinus mucosa. An overall success rate of 85% is reported in primary functional endoscopic sinus surgery, with a 2% to 24% failure rate because of recurrence of disease or poor healing because of persistent infl ammation and/or bacterial colonization [46,47]. In approximately 18% of patients, poor healing is linked to abnormal scarring, superinfection, and fi brosis formation, with these complications potentially leading to revision surgery [48].…”
Section: Treatmentmentioning
confidence: 99%
“…Despite a high initial success rate, 10% to 15% of patients who undergo FESS will undergo revision surgery . Revision FESS is often considered to have an increased risk of complications due to altered anatomy and scarring . In one retrospective study of 90 patients, revision surgery was found to be a significant risk factor for CSF leak .…”
Section: Introductionmentioning
confidence: 99%
“…These factors are magnified as the probe is moved further from the sensor on the headset. In our VTI endoscopic surgery series the overall accuracy was ±0.7 mm in the cranial‐caudal axis, and ±0.45 mm in all other axes 10 . Occasionally during the case the surgeon will be warned if an excess of metal in the nose is affecting the electromagnetic sensor.…”
Section: Discussionmentioning
confidence: 88%
“…This technology allows for the visualization of the surgeon's probe in all three orthogonal planes, in real time. We have reviewed our large series of endoscopic surgeries utilizing VTI's (Visualization Technology, Inc.) Instatrak three‐dimensional localization system and have found it to be very accurate and helpful in the majority of cases 10 . We have recently collaborated with the department of neurosurgery to utilize an endoscopic approach and apply intraoperative localization technology to pituitary surgery.…”
Section: Introductionmentioning
confidence: 99%